Efektivitas Layanan Bimbingan Pranikah terhadap Kesiapan Mental Calon Pengantin untuk Membentuk Keluarga Sakinah di Kantor KUA Kecamatan Kumpeh Ulu, Kab. Muaro Jambi : Penelitian - Syarifah Syamilah; Sitti Aminah; Cindy Melinda; Evi Yulia Fitri; Ratna Pertiwi; Nurul Khotimah; Budiman Halim (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Marriage is a fundamental social institution that serves as a legal bond and the foundation for family formation, generational continuity, and social harmony. Marriage is defined as a physical and spiritual bond between a man and a woman to form a happy, eternal family based on divine values. This study aims to determine the implementation process and the results of the influence of premarital guidance for prospective brides and grooms at the Kumpeh Ulu District Office of Religious Affairs (KUA) in forming a harmonious family. The study used qualitative methods through in-depth interviews. The results showed that premarital guidance at the Kumpeh Ulu District Office of Religious Affairs (KUA) is quite effective through a group system and collaboration with officers, with routine guidance every Tuesday that includes education on marital rights and obligations, household communication, financial management, and reproductive health.